RANCANGAN SISTEM INFORMASI PENJUALAN FUTAMI 17 GREEN TEA PADA PT. MANNA DISTRINDO - Irma Suana (JURNAL AKADEMIKA)
PT . Manna Distrindo in data processing sales Futami 17 Green Tea has been using the computer where the application being used is Microsoft Word and Microsoft Excel . But by using both of the above application had not been optimal , this situation often occurs due to the difference between the sale in accordance with the type of outlet .For that here the author tries to give advice to PT. Manna Distrindo using Microsoft Visual Basic 6.0 .Where later can help complete the work on the PT . Manna Distrindo as well as more effective and efficient in terms of both time and cost , also in conveying information to the hands of the leadership quickly.